2013
DOI: 10.1103/physrevd.87.071503
|View full text |Cite
|
Sign up to set email alerts
|

Conformal theories with an infrared cutoff

Abstract: We give a new perspective on the dynamics of conformal theories realized in the SU(N ) gauge theory, when the number of flavors N f is within the conformal window. Motivated by the RG argument on conformal theories with a finite IR cutoff ΛIR, we conjecture that the propagator of a meson GH (t) on a lattice behaves at large t as a power-law corrected Yukawa-type decaying form GH(t) =cH exp (−mHt)/t α H instead of the exponentially decaying form cH exp (−mHt), in the small quark mass region where mH ≤ c ΛIR: mH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
(9 reference statements)
4
26
0
Order By: Relevance
“…In particular, the above two-loop/ladder studies would suggest that the walking theory if existed might be in between N f = 8 and N f = 12. As to N f = 12 there have been many analyses including those of ourselves which are consistent with the theory being inside the conformal window [10,11,[15][16][17][18][19][20][21][22][23][24], although some works prefer the SχSB phase [25,26]. There were also simulations on N f = 10 [27] consistent with the infrared conformality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the above two-loop/ladder studies would suggest that the walking theory if existed might be in between N f = 8 and N f = 12. As to N f = 12 there have been many analyses including those of ourselves which are consistent with the theory being inside the conformal window [10,11,[15][16][17][18][19][20][21][22][23][24], although some works prefer the SχSB phase [25,26]. There were also simulations on N f = 10 [27] consistent with the infrared conformality.…”
Section: Introductionmentioning
confidence: 99%
“…To date, some groups carried out lattice studies on 8-flavors, with Wilson fermions [10,11,23,24] and with staggered fermions [12,15,25,26,[31][32][33][34]. The Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scaling of (1/L), where L is a finite lattice extent, tells us whether the theory is conformal or not in the infinite volume limit. The other independent method has also been suggested in the paper [10]. The authors gave a conjecture that the correlation function of the mesonic operator in the finite volume around the IRFP becomes the Yukawa-type function not an exponential form.…”
Section: • Shape Of the Correlation Function Of Mesonic Operatormentioning
confidence: 99%
“…The volume scaling for the Dirac eigenmodes [9] and the shape of the mesonic correlation function [10,23] also show the signal of the IRFP. In the studies of SU(3) gauge theory with N f = 7 and 10 [24,25,26], they found a signal of the conformality for each theory.…”
Section: Pos(lattice 2013)005mentioning
confidence: 99%